Microtus oeconomus - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Microtus oeconomus (Pallas, 1776). Reise Prov. Russ. Reichs., 3:693. TYPE LOCALITY: Siberia, Ishim Valley. DISTRIBUTION: Tundra and northern taiga of Holarctic: in Palearctic, from Scandinavia and the Netherlands across to borderlands of Bering Sea, including Sakhalin and Kurile islands, and south to E Germany, Ukraine, S Kazakhstan, Mongolia, and the Ussuri region; St. Lawrence Isl in Bering Sea; in Nearctic, from Alaska through Yukon Territory to W Northwest Territories and extreme NW British Columbia, Canada. SYNONYMS: altaicus, amakensis, anikini, arenicola, dauricus, elymocetes, endoecus, finmarchicus, flaviventris, gilmorei, hahlovi, innuitus, kamtschatica, karaginensis, kjusjurensis, kodiacensis, koreni, macfarlani, malcolmi, médius, mehelyi, montium-caelestinum, naumovi, operarius, ouralensis, petshorae, popofensis, punukensis, ratticeps, shantaricus, sitkensis, stimmingi, suntaricus, tschuktschorum, uchidae, unalascensis, uralensis, yakutatensis. COMMENTS: Subgenus Pallasiinus, oeconomus species group, including M. montebelli and M. limnophilus (Zagorodnyuk, 1990). Conspecific stature of Old and New World populations averred by Zimmermann (1942) and sustained by subsequent studies (Nadler et al., 1976, 1978; Ognev, 1964; Rausch, 1953). Geographic variation and subspecies of Nearctic populations reviewed by Paradiso and Manville (1961); Russian populations by Gromov and Polyakov (1977); European populations by Tast (1982b). Chromosomal data is summarized and evaluated by Zima and Krâl (1984a). Ecological and distributional details of the species at its southern limit in Poland are described by Salata-Pilacinska (1990). Angermann (1984) analysed intraspecific molar patterns in the context of assessing the range of variation against which patterns in extinct species could be tested. Ognev (1964), but not Corbet (1978c), identified ratticeps Keyserling and Blasius, 1841, as the proper name applicable to this species (also see discussions in Ellerman and Morrison-Scott, 1951:705; and Hall, 1981:805). ...